Pengaruh Pendapatan, Literasi Keuangan, Locus of Control dan Kepribadian Terhadap Perilaku Manajemen Keuangan UMKM Coffee Shop di Wilayah Surakarta - Ismawati, Adinda Fadhilla; Rochman, Arif Nugroho (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
This research aims to analyze the influence of income, financial literacy, locus of control and personality on financial management behavior among MSME coffee shop operators in Surakarta. The population of this research is MSME Coffee Shops in Surakarta. The data used is primary data obtained through interviews and submitting statements that have been prepared by distributing questionnaires and using quantitative methods. The results of this research show that there is a negative influence between income on financial management behavior, while financial literacy, locus of control and personality have a positive influence on financial management behavior